The Capital / Logic Debate - Blunden, Andy (Social Sciences E-Books Online, Collection 2026, 2025)
Here, Andy Blunden presents the first of two volumes on how Marx used Hegel's Logic in his Capital . In this first volume, Blunden reviews the current literature on the topic with detailed reviews of the contribution of 10 authors, representing the spectrum of approaches. Finding that present-day writers fail to understand the Logic and misrepresent Capital as a work of Logic, Blunden focuses on the passage in the Logic entitled "The Idea of the True," which is ignored by every writer in the present-day debate.